2009
DOI: 10.1371/journal.pone.0007142
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Bronchus-Associated Lymphoid Tissue Elicited by a Protein Cage Nanoparticle Enhances Protection in Mice against Diverse Respiratory Viruses

Abstract: BackgroundDestruction of the architectural and subsequently the functional integrity of the lung following pulmonary viral infections is attributable to both the extent of pathogen replication and to the host-generated inflammation associated with the recruitment of immune responses. The presence of antigenically disparate pulmonary viruses and the emergence of novel viruses assures the recurrence of lung damage with infection and resolution of each primary viral infection. Thus, there is a need to develop saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
171
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(187 citation statements)
references
References 19 publications
12
171
2
2
Order By: Relevance
“…Strikingly, LPS exposure in neonatal and weanling mice significantly diminished viral burden in response to acute Pneumovirus infection later in life, and decreased the magnitude of sloughing of the airway epithelium, consistent with a protective role for iBALT. Our findings are in agreement with previous reports demonstrating that BALT can confer protection against various respiratory viruses and limit immunopathology (3)(4)(5). Although the mechanistic basis for this phenomenon remains to be definitively elucidated, we observed that the increased presence of iBALT was associated with increased expression of the neutrophil chemokines CCL3 and CXCL10, a heightened neutrophilia, and elevated IFN-g expression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Strikingly, LPS exposure in neonatal and weanling mice significantly diminished viral burden in response to acute Pneumovirus infection later in life, and decreased the magnitude of sloughing of the airway epithelium, consistent with a protective role for iBALT. Our findings are in agreement with previous reports demonstrating that BALT can confer protection against various respiratory viruses and limit immunopathology (3)(4)(5). Although the mechanistic basis for this phenomenon remains to be definitively elucidated, we observed that the increased presence of iBALT was associated with increased expression of the neutrophil chemokines CCL3 and CXCL10, a heightened neutrophilia, and elevated IFN-g expression.…”
Section: Discussionsupporting
confidence: 93%
“…This is somewhat surprising as neutrophils are one of the first inflammatory cells to be recruited to the site of sterile or infectious inflammation, can migrate from the inflammatory site to the draining lymph nodes, and are increasingly recognized as modulators of adaptive immunity (42)(43)(44). Indeed, neutrophils have been observed to infiltrate the iBALT area (12,45) as well as other TLOs (46,47), and are recruited in response to other TLR ligands or infectious pathogens shown to initiate iBALT formation in various animal species (4,48). Perhaps most significantly, neutrophilic inflammation is a common feature of diseases in which iBALTs are prevalent, including COPD, rheumatoid arthritis, asthma, idiopathic pulmonary fibrosis, tuberculosis, and hypersensitivity pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 It has been shown that iBALT can functionally replace the function of conventional lymphoid organs and its size and cell composition varies widely. 37,38 Thus, the appearance of iBALT in our experiment might be related to the observed hypertrophy and fibrotic changes in thymus.…”
Section: Discussionmentioning
confidence: 53%
“…However, the lung is able to mount its own immune responses in situ, without secondary lymphoid tissues (11,12). This is attributable to the development of inducible bronchus-associated lymphoid tissue (iBALT), which contains a full complement of antigen-presenting cells (i.e., B and T cells) that are able to induce local humoral and cellular immunity (13,14). As such, the lung may function as a "lymph node with alveoli" (15).…”
Section: Initiation Of the Immune Response In Lung Allograftsmentioning
confidence: 99%